As TIC na formação docente: fundamentos para o design de objetos virtuais de aprendizagem - Souza, Liliane de Oliveira (2016)
Faced with the exponential growth of technology in daily activities, teachers have to find out possibilities of including it in their classes. However, teachers need to have understanding and awareness of the potential but also the limits of technology in education, and these elements must be acquired and learned initially in the initial training process. With steps of participatory research, this study analyzes a teacher training proposal for the use of ICT in mathematics teaching, and as a resource produced, virtual learning objects (VLO) to be used in classes of basic education. The participants were students of Teaching Degree in Mathematics, State University of Goiás/Campus Cora Coralina, whose training needs, related to the knowledge required for the use of ICT in the classroom, were identified. The proposed training based on the use of ICT in mathematics classes was developed in the subject of Digital Media in Mathematics Education (annual and on the classroom) in partnership with the subject Supervised Internship I, both taught by the teacher-researcher. It was used a supplementary space for discussion the subject Digital Media in Mathematics Education, Modular Object Oriented Dynamic Learning (Moodle). We used this virtual platform aiming at the acquisition of knowledge necessary for planning and development of contextual VLO to be applied during the supervised training of those involved. The VLO were developed addressing the themes: civil construction - for discussion of plane geometry concepts; planning a party - using concepts and applications of the 1st and 2nd degree functions; and financial mathematics - used to analyze the purchase of a property. Our findings pointed that one of the conditions for the use of ICT in education is the active participation of the teacher in the development of the material from the joint theoretical reflection of its operating context, resulting in the understanding of the need to approximate the content to be taught to the students’ daily lives.